TARIAN TRADISIONAL SINGA MASYARAKAT CINA KUCHING - CHUA, SEOK FANG (Universiti Malaysia Sarawak, (UNIMAS), 2016)
The research title is Chinese Traditional Lion Dance in Kuching. This research is mainly about the Chinese lion dance in Kuching. In particular, this research focus on the lion dance of Association Dragon Dance, Lion Dance, and Wushu Sarawak (PTNSWS). Aim of this research is to identify the concept of the lion dance in terms of meaning and function as well as the origin of the lion dance. In addition, the research also aims to study the management of the lion dance in PTNSWS. The research is conducted through the methods of observation and interview as well as through methodology method of fieldwork in PTNSWS. This research had interviewed five informants who are experienced and knowledgeable in lion dance as well as the management of the lion dance. The research outcomes show that the management of lion dance in PTNSWS is very systematic in terms of production, human resources, finance and marketing.